2021
DOI: 10.1088/1748-605x/ab9f57
|View full text |Cite
|
Sign up to set email alerts
|

A photoactivatable antibody–Chlorin e6 conjugate enabling singlet oxygen production for tumor-targeting photodynamic therapy

Abstract: Photodynamic therapy is a new technology for disease diagnosis and treatment in modern medical clinics. The main advantages of photodynamic therapy are low toxicity and side effects, a wide range of applications, no drug resistance, and no obvious trauma in the treatment process. However, to achieve effective photodynamic therapy, new photosensitizer carriers need to be constructed, which can selectively deliver photosensitizers into tumor tissues. In this work, a photoactivatable antibody–Chlorin e6 conjugate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…Preliminary tests using sub-micromolar concentrations resulted in no significant effects and are not reported. This is in line with previously published works, where Atezolizumab [36,37] was used in definitely larger concentrations than the dissociation constant of the antibody, 0.19 nM and 0.62 nM for the dimeric and monomeric form of PD-L1, respectively [35].…”
Section: Photoinactivation Treatment With the Conjugatesupporting
confidence: 92%
See 2 more Smart Citations
“…Preliminary tests using sub-micromolar concentrations resulted in no significant effects and are not reported. This is in line with previously published works, where Atezolizumab [36,37] was used in definitely larger concentrations than the dissociation constant of the antibody, 0.19 nM and 0.62 nM for the dimeric and monomeric form of PD-L1, respectively [35].…”
Section: Photoinactivation Treatment With the Conjugatesupporting
confidence: 92%
“…The ATP assay performed 3 and 24 h after illumination (Figure 3E) and the MTT assay (Figure 3F) suggested that the photoinactivation was a little more efficient in A549 than in H322 cells when the conjugate was used at 5 µM, while the effect was comparable between the two models at 10 µM, within the error bars. Similar results were reported by Pan et al using a Chlorin-e6-functionalized Atezolizumab at the same concentrations on HCT-116 cells [36].…”
Section: Photoinactivation Treatment With the Conjugatesupporting
confidence: 89%
See 1 more Smart Citation
“…The conjugate demonstrated anti-tumor efficacy in HCT-116 (colon cancer cell line) tumor-bearing mouse model showing a tumor mass reduction greater than 50% compared to the same conjugate treatment without light activation. No data about the conjugate adverse effects in vivo were reported ( Pan et al, 2021 ).…”
Section: Atezolizumabmentioning
confidence: 99%
“…In addition to the passive accumulation, nanoparticles with active targeting performance are also employed to deliver drugs, by modifying specific ligands with high affinity to cancer cells ( e.g. polypeptides ( Fang et al, 2020 ; Kang et al, 2020 ), proteins, antibodies ( Chen et al, 2012 ; Pan et al, 2021 ), folic acids ( Mitra et al, 2018 ) and aptamers ( Tang et al, 2020 ; Tian et al, 2021 )). On this basis, the unique advantages of nanocarriers have been widely demonstrated including long-term sustained ( Xia et al, 2019 ) and controlled release ( Xia et al, 2014 ) and the integration with more diagnostic or therapeutic modality such as multimodal imaging ( Gao et al, 2017 ; Xia et al, 2017 ; Liu et al, 2019 ), photodynamic therapy (PDT) ( Lucky et al, 2015 ; Wen et al, 2020 ), photothermal therapy (PTT) ( Xia et al, 2016 ; Yang et al, 2017 ) and immunotherapy ( Meraz et al, 2012 ; Secret et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%